Field Evaluation of Synthetic Insecticides for Effective Management of Sucking Insect Pests in Okra (Abelmoschus esculentus L.) Cultivation - Khan, Fawad; Ahmad, Ayaz; Jakhrani , Abdul Nabi; Shabana, Noor; Usman, Muhammad; Pervez, Mahnoor; Nawaz, Kamran; Nazeef, Sumbal (Andalasian International Journal of Entomology, 2025)
Aphid (A. gossypii) is the major pest of okra. It took the top position among all the vegetable pests. The study assessed the effectiveness of synthetic insecticides for controlling sucking insect pests and their natural enemies in okra cultivation. Conducted at the Agriculture University, Peshawar, the experiment employed a randomized complete block design (RCBD) with five treatments: Deltamethrin, Malathion, Lambda-Cyhalothrin, Emamectin Benzoate, and a control. Infestation levels were recorded before spraying and at regular intervals after application. Results showed that Emamectin Benzoate was the most effective, consistently achieving the lowest infestation levels compared to other treatments. It reduced infestation from 81.75 before spraying to 43.53 after 15 days. It also resulted in the highest yield (3,900.59 kg/ha), outperforming other insecticides, such as Deltamethrin (2,978.56 kg/ha), Malathion (2,888.44 kg/ha), and Lambda Cyhalothrin (2,505.55 kg/ha). The control group had the lowest yield (526.70 kg/ha). Emamectin Benzoate also supported the growth of beneficial ladybird beetles, particularly Coccinella transversalis and C. septempunctata, whose populations peaked in week 3. Emamectin Benzoate was the most effective insecticide for managing sucking pests and improving yield in okra cultivation, supporting its role in integrated pest management strategies.